The Use of Board Game as a Teaching Technique for Assisting Ninth Graders Speaking Ability - Masyhuroh, Luisita Khadlrotul (RETAIN : Journal of Research in English Language Teaching, 2022)
Speaking is one of the English skills besides listening, reading, and writing. It is an activity to generate language and share ideas orally. In this study, the researches show that an attractively packaged “Board Game” will make it easier for students to speak up. The method used is using qualitative and conducting research in one of the MTs schools in Gresik. In this study, the teacher conducted pre-teaching, teaching, and post-teaching exercises. The use of “Board Game” occurs during pre-teaching and teaching. The material used in this game is to ask for and give information related to conditions, activities, and actions in the present. In the final stage, the teacher provides the application of the use of speaking skills assessment rubrics. Many students dare to speak and achieve the desired target. Based on these findings, the researcher concluded that the “Board Game” can be used as a teaching technique to help students in speaking practice particularly related to asking for and giving information about current conditions, activities, and actions.